Swiftness and Delay of Punishment - Libor Dušek; Christian Traxler (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper studies how the swiftness and delay of punishment affect behavior. Using rich administrative data from automated speed cameras, we exploit two (quasi-)experimental sources of variation in the time between a speeding offense and the sending of a ticket. At the launch of the speed camera system, administrative challenges caused delays of up to three months. Later, we implemented a protocol that randomly assigned tickets to swift or delayed processing. We identify two different results. First, delays have a negative effect on payment compliance: the rate of timely paid fines diminishes by 7 to 9% when a ticket is sent with a delay of four or more weeks. We also find some evidence that very swift tickets – sent on the first or second day following the offense – increase timely payments. These results align with the predictions of expert scholars that we elicited in a survey. Second, speeding tickets cause a strong, immediate, and persistent decline in speeding. However, we do not detect any robust, differential effects of swiftness or delay on speeding. This challenges widely held beliefs, as reflected in our survey. Yet, we document large mechanical benefits of swift punishment and provide a theoretical framework of learning and updating that explains our findings.
Keywords: K14; K42; D80; 330; law enforcement; celerity of punishment; swiftness; specific deterrence; speeding; payment compliance; expert survey